Pemanfaatan Serbuk Kayu untuk Produksi Etanol dengan Perlakuan Pendahuluan Delignifikasi Menggunakan Jamur Phanerochaete Chrysosporium - Denny Irawati; Norman Razief Azwar; Wasrin Syafii; I Made Artika (Jurnal Ilmu Kehutanan, 2009)
Utilization of Sawdust to Produce Ethanol Using Delignification Pre-treatment with White Rot Fungi Phanerochaete chrysosporiumCurrently, Indonesia is in the middle ofpetroleum crisis. One ofthe alternative fuels which can be used as a petroleum substitute is ethanol. Ethanol can be produced from timber waste (sawdust). Indonesia in 2003 had timber waste potency of about 3-4 millions m3. However, ethanol production from sawdust has problems due to its lignin content. Therefore, research on bio-delignification treatment of sawdust prior to ethanol making process is required. In the present study ethanol was produced by simultaneous saccharification and fermentation (SSF) using crude cellulose from Trichoderma viride and Saccharomyces cerevisiae. The raw materials for ethanol production are sengon (Paraserianthes falcataria (L.) Nielsen syn.), meranti (Shorea sp.) and teak (Tectona grandis LIIVN.f.) sawdust after pretreatment with white rot fungi Phanerochaete chrysosporium for 10, 20 and 30 days incubation time. The yield of ethanol was between 1.65-44.83 g/1. The best combination treatment is sengon sawdust with 30 day incubation time.